Preparation method of cellulose nanocrystalline composite material and adopted device
By injecting reaction solution containing calcium ion aqueous solution and cellulose nanocrystals into the hydrogel plate, high-strength and high-strength cellulose nanocrystal composite fibers into a hydrogel plate, the problem of insufficient mechanical strength of existing cellulose nanocrystal composite fibers is solved, and high-strength and biodegradable characteristics are achieved.
Patent Information
- Application Number
- CN202411686542.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The mechanical strength of the cellulose nanocrystal composite fibers prepared at this stage is poor, which is lower than that of natural cellulose materials, limiting the practical application of cellulose nanocrystals.
By providing side-by-side grooves on the L-shaped structure of the hydrogel plate, the hydrogel plate soaked with calcium ion aqueous solution is used as a substrate, the reaction solution is injected to form gel fibers, and treated in a water bath to prepare high-strength, high-strength, high-strength, and high-strength cellulose nanocrystal composite fibers.
It has achieved high strength and high toughness of cellulose nanocrystal composite fibers and has biodegradable properties, which has expanded its application fields.
Smart Images

Figure CN119507078A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber materials, and in particular relates to a preparation method of a cellulose nanocrystal composite material and a device used therein. Background Art
[0002] Cellulose is the most abundant natural biomass material on earth and has excellent mechanical properties, specific modulus (about 100 GPa·g / cm 3 ) and specific strength (about 4GPa·g / cm 3 ) exceeds most ceramics, metals and their composites. In particular, cellulose nanocrystals produced by acid hydrolysis of cellulose, during the acid hydrolysis of cellulose, the disordered non-crystalline regions and quasi-crystalline regions of the polymer chain are preferentially hydrolyzed, while the crystalline regions with higher resistance to acid attack remain intact. Therefore, compared with cellulose nanofibers, cellulose nanocrystals usually present a unique rod-like or needle-like morphology, with a length ranging from tens to hundreds of nanometers and a diameter in the range of several nanometers. Due to the removal of most of the non-crystalline regions during the preparation of cellulose nanocrystals, the crystallinity in CNC ranges from 54% to 88%, so the axial stiffness of CNC is 105-168GPa and the tensile strength is about 9Gpa.
[0003] At present, scientists have developed dry spinning, wet spinning, microfluidics and other methods to prepare high-strength and tough nanocomposite fibers. In the prior art, CNC-CNF composite fibers are prepared by dry spinning and physically cross-linked by polyamide-epichlorotrioxane. The composite fiber has a breaking strength of 369.8MPa and a Young's modulus of 28.9GPa. In the prior art, CNC and PVA composite fibers are prepared by wet spinning, with a maximum tensile strength of 356.34MPa. In the prior art, microfluidics technology is used to realize the wet spinning of CNC fibers for the first time, with an average Young's modulus of 1263cN·tex -1 Breaking strength: 10.6 cN·tex -1 , which is twice that of ordinary CNC. However, the mechanical strength of the cellulose nanocrystal composite fibers prepared at this stage is usually poor, significantly lower than the mechanical properties of natural cellulose materials, which limits the practical application of cellulose nanocrystals.
[0004] At present, the performance of CNC composite materials in extreme environments, long-term stability and durability, and compatibility with other materials are still understudied, and more experiments and research are needed to reveal their essential laws. With the continuous advancement of science and technology and the improvement of people's requirements for material performance, the application field of CNC composite materials needs to be further expanded. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a cellulose nanocrystal composite material and an adopted device. The cellulose nanocrystal composite fiber obtained by the method provided by the present invention has the characteristics of high strength, high toughness and biodegradability.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing cellulose nanocrystal composite fibers, comprising the following steps:
[0008] A hydrogel plate is provided as a substrate, wherein a plurality of grooves arranged side by side are arranged on the surface of the substrate; the hydrogel plate is in an L-shaped structure;
[0009] After the substrate is swelled to saturation in an aqueous solution containing calcium ions, a reaction solution is injected into the vertical grooves of the hydrogel plate, and the gel fibers formed by the grooves are bathed in water to obtain the cellulose nanocrystal composite fibers;
[0010] The reaction solution comprises cellulose nanocrystals, water-soluble polymers, sodium alginate and water.
[0011] Preferably, the hydrogel plate is a polyacrylamide hydrogel plate; the groove is a circular groove with a diameter of 0.4 to 1.0 mm.
[0012] Preferably, the concentration of calcium ions in the calcium ion-containing aqueous solution is 0.5 to 3 mol / L.
[0013] Preferably, the cellulose nanocrystals are in a nanorod structure, and the length of the nanorod structure is 315±42 nm and the diameter is 6.2±1.6 nm.
[0014] Preferably, the water-soluble polymer includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose and water-soluble polyurethane.
[0015] Preferably, the viscosity of the sodium carboxymethyl cellulose is 3000-5000 mpa·s;
[0016] The weight average molecular weight of the polyvinyl alcohol is 14.6-18.6w;
[0017] The solid content of the water-soluble polyurethane is 37-39%.
[0018] Preferably, the viscosity of the sodium alginate is 180-220 mpa·s.
[0019] Preferably, the mass ratio of the water-soluble polymer to sodium alginate is 10:3-10;
[0020] When the water-soluble polymer is sodium carboxymethyl cellulose, the mass ratio of the cellulose nanocrystals to the water-soluble polymer is 3 to 15:100;
[0021] When the water-soluble polymer is polyvinyl alcohol or water-soluble polyurethane, the mass ratio of the cellulose nanocrystals to the water-soluble polymer is 5 to 15:100;
[0022] The mass ratio of the cellulose nanocrystals to water is 3-15:10000.
[0023] Preferably, after the water bath, the obtained wet fiber is dried.
[0024] The present invention also provides a device used in the preparation method described in the above technical solution, comprising:
[0025] A hydrogel plate, wherein a plurality of grooves arranged side by side are arranged on the surface of the hydrogel plate, and the hydrogel plate is in an L-shaped structure;
[0026] A reaction liquid syringe array, wherein the syringes in the reaction liquid syringe array are connected to the vertical grooves on the hydrogel plate in a one-to-one correspondence through pipelines;
[0027] Water bath.
[0028] The invention provides a method for preparing cellulose nanocrystal composite fibers, comprising the following steps: providing a hydrogel plate as a substrate, wherein a plurality of side-by-side grooves are arranged on the surface of the substrate; the hydrogel plate is in an L-shaped structure; after the substrate is swelled to saturation in a calcium ion-containing aqueous solution, a reaction liquid is injected into the vertical grooves in the hydrogel plate, and the gel fibers formed by flowing through the grooves are subjected to a water bath to obtain the cellulose nanocrystal composite fibers; the reaction liquid comprises cellulose nanocrystals, a water-soluble polymer, sodium alginate and water.
[0029] The present invention provides a high-strength, high-toughness, biodegradable, and fully bio-based composite material with large-area production capacity. The present invention allows an aqueous solution containing cellulose nanocrystals (CNC), calcium alginate (SA), and a water-soluble polymer to flow rapidly and directionally on a vertical, grooved surface containing a hydrogel; at the same time, as calcium ions diffuse from the hydrogel surface into the liquid film, the reaction liquid is rapidly gelled into gel fibers through in-situ ionic crosslinking of sodium alginate (calcium ions crosslink with sodium alginate to form a calcium alginate network, fix the oriented rod-shaped cellulose nanocrystals, and solidify the fibers), and the gel fibers are easily separated from the surface of the hydrogel substrate in a water bath (water and the gel substrate are immiscible). Finally, the formed gel film is separated from the hydrogel substrate, and cleaned and dried, and finally a CNC composite material with an oriented arrangement structure is prepared.
[0030] The present invention allows an aqueous solution containing CNC, SA and a water-soluble polymer to flow rapidly and directionally on a vertical, grooved surface containing a hydrogel, thereby inducing CNC to assemble into a highly ordered structure. 2+ The hydrogel's super-hydrophilic properties in the air, combined with its surface-replicated micron-scale groove structure, utilize the shear flow generated when the aqueous solution spreads rapidly in the grooves on the surface of the hydrogel. Under the synergistic effect of the confined space provided by the grooves, the rod-shaped CNC is highly oriented. At the same time, due to the casting effect of the shear flow on the water-soluble polymer and SA, the stable connection between CNC and the water-soluble polymer and SA molecules can be ensured, forming more hydrogen bonds. At the same time, during the downward flow of the solution, SA and Ca 2+ The diffusion cross-linking with sulfonic acid and carboxyl groups forms a gel film, which not only enhances the mechanical properties of the material but also improves its stability in aqueous environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic diagram of a device for preparing a cellulose nanocrystal composite material provided by the present invention;
[0032] Figure 2 Schematic diagram of preparation of different hydrogel substrate groove inclination angles in Example 1 and Comparative Example 1;
[0033] Figure 3 The azimuth angle curves of the composite fiber samples prepared with different hydrogel substrate groove inclination angles in Example 1 and Comparative Example 1;
[0034] Figure 4 The electron diffraction images of composite fiber samples prepared with different hydrogel substrate groove inclination angles under different inclination angles in Example 1 and Comparative Example 1;
[0035] Figure 5 Polarized light microscope test pictures of composite fiber samples prepared with different hydrogel substrate groove inclination angles in Example 1 and Comparative Example 1;
[0036] Figure 6 Orientation parameters calculated for composite fiber samples prepared at different hydrogel substrate groove inclination angles in Example 1 and Comparative Example 1;
[0037] Figure 7 The tensile stress-strain curves of the composite fibers prepared at different CMC-SA ratios in Comparative Example 2;
[0038] Figure 8 is the tensile stress-strain curve of the cellulose nanocrystal composite fiber obtained in Examples 1 to 4;
[0039] Fig. 9is the azimuth angle curve of the cellulose nanocrystal composite fiber obtained in Examples 1 to 4;
[0040] Fig.10 is the calculated orientation parameter of the cellulose nanocrystal composite fibers obtained in Examples 1 to 4;
[0041] Fig.11 The scanning electron microscope (SEM) image and element distribution diagram of the composite fiber obtained in Example 1;
[0042] Fig.12 The decomposition of the nanocomposite fibers obtained in Example 1 on the paper tube and the comparison of the decomposition rate of the paper tube are shown in FIG. DETAILED DESCRIPTION
[0043] The present invention provides a method for preparing cellulose nanocrystal composite fibers, comprising the following steps:
[0044] A hydrogel plate is provided as a substrate, wherein a plurality of grooves arranged side by side are arranged on the surface of the substrate; the hydrogel plate is in an L-shaped structure;
[0045] After the substrate is swelled to saturation in an aqueous solution containing calcium ions, a reaction solution is injected into the vertical grooves of the hydrogel plate, and the gel fibers formed by the grooves are bathed in water to obtain the cellulose nanocrystal composite fibers;
[0046] The reaction solution comprises cellulose nanocrystals, water-soluble polymers, sodium alginate and water.
[0047] The present invention provides a hydrogel plate as a substrate, wherein a surface of the substrate is provided with a plurality of side-by-side grooves; the hydrogel plate is in an L-shaped structure.
[0048] In the present invention, the hydrogel plate is preferably a polyacrylamide hydrogel plate; the groove is preferably a circular groove, and the diameter is preferably 0.4-1.0 mm, specifically 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm.
[0049] In the present invention, the polyacrylamide hydrogel sheet is preferably prepared by a method which preferably comprises the following steps:
[0050] 15 g of acrylamide monomer, 0.3 g of N,N'-methylenebisacrylamide (cross-linking agent) and 0.3 g of ammonium persulfate (catalyst) were dissolved in 100 mL of deionized water and mixed evenly; then 300 μL of N,N,N',N'-tetramethylethylenediamine (initiator) was added, mixed evenly, poured into a mold, and polymerized at room temperature for 5 minutes; then it was immersed in deionized water to remove unreacted monomers and fully swelled to prepare the polyacrylamide hydrogel plate.
[0051] After obtaining the substrate, the present invention swells the substrate to saturation in a calcium ion-containing aqueous solution, injects the reaction solution into the vertical grooves in the hydrogel plate, and the gel fibers formed by flowing through the grooves are subjected to a water bath to obtain the cellulose nanocrystal composite fibers.
[0052] In the present invention, the concentration of calcium ions in the calcium ion-containing aqueous solution is preferably 0.5 to 3 mol / L. The present invention has no particular limitation on the amount of the calcium ion-containing solution, as long as it can swell the hydrogel sheet to saturation.
[0053] In the present invention, the reaction solution comprises cellulose nanocrystals, water-soluble polymers, sodium alginate and water.
[0054] In the present invention, the cellulose nanocrystals are preferably in a nanorod structure, and the length of the nanorod structure is preferably 315±42 nm, and the diameter is preferably 6.2±1.6 nm.
[0055] In the present invention, the cellulose nanocrystals are preferably prepared by a method which preferably comprises the following steps:
[0056] The cellulose microcrystals are mixed with sulfuric acid and subjected to acid hydrolysis to obtain the cellulose nanocrystals.
[0057] In the present invention, the particle size of the cellulose microcrystals is preferably 50 μm. In the present invention, the sulfuric acid concentration is preferably 64 wt %. The present invention has no particular limitation on the amount of sulfuric acid used, and any amount known to those skilled in the art may be used. In the present invention, the acid hydrolysis time is preferably 45 to 60 min. In the present invention, the amorphous region in the cellulose can be removed by acid hydrolysis to obtain the crystalline region, i.e., the rod-shaped cellulose nanocrystal.
[0058] In the present invention, the water-soluble polymer preferably includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose and water-soluble polyurethane. In the present invention, the viscosity of the sodium carboxymethyl cellulose is preferably 3000-5000 mPa·s; the weight average molecular weight of the polyvinyl alcohol is preferably 14.6-18.6w; the solid content of the water-soluble polyurethane is preferably 37-39%. In the present invention, the viscosity of the sodium alginate is preferably 180-220 mPa·s.
[0059] In the present invention, the mass ratio of the water-soluble polymer to sodium alginate is preferably 10:3-10, specifically 10:3, 10:4, 10:5, 10:6, 10:7, 10:8, 10:9, 10:10; when the water-soluble polymer is sodium carboxymethyl cellulose, the mass ratio of the cellulose nanocrystal to the water-soluble polymer is preferably 3-15:100, specifically 3:100, 5:100, 8:100, 10:100, 12:100, 15:100; when When the water-soluble polymer is polyvinyl alcohol or water-soluble polyurethane, the mass ratio of the cellulose nanocrystals to the water-soluble polymer is preferably 5-15:100, specifically 5:100, 8:100, 10:100, 12:100, 15:100; the mass ratio of the cellulose nanocrystals to water is preferably 3-15:10000, specifically 3:10000, 5:10000, 8:10000, 10:10000, 12:10000, 15:10000.
[0060] In the present invention, the reaction liquid is preferably continuously injected into the groove by a syringe. The present invention has no special limitation on the process of the water bath, and the process well known to those skilled in the art can be used. In the present invention, after the water bath, the wet fiber is preferably dried. In the present invention, the drying is preferably carried out in air, and the humidity of the air is preferably 20% to 40% RH.
[0061] In the present invention, the cellulose nanocrystal composite fiber preferably includes the following components in percentage by weight: 1.8-8.5% of cellulose nanocrystals (CNC), 34.3-36.8% of sodium alginate (SA), and 57.2-61.4% of a water-soluble polymer.
[0062] The present invention also provides a device used in the preparation method described in the above technical solution, comprising:
[0063] A hydrogel plate, wherein a plurality of grooves arranged side by side are arranged on the surface of the hydrogel plate, and the hydrogel plate is in an L-shaped structure;
[0064] A reaction liquid syringe array, wherein the syringes in the reaction liquid syringe array are connected to the vertical grooves on the hydrogel plate in a one-to-one correspondence through pipelines;
[0065] Water bath.
[0066] In the present invention, the device preferably further comprises a fiber receiving member.
[0067] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0068] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0069] In the following examples, plant materials were purchased from Sigma-aldrich, sodium alginate (SA) and sodium carboxymethyl cellulose (CMC) were purchased from MacLean Biotechnology Co., Ltd.
[0070] Example 1
[0071] use Figure 1 The device shown is used to prepare cellulose nanocrystal composite fibers;
[0072] Mixing cellulose microcrystals with a particle size of 50 μm and sulfuric acid with a mass concentration of 64 wt%, and performing acid hydrolysis for 45 minutes to obtain the cellulose nanocrystals, wherein the cellulose nanocrystals are in the shape of nanorods with a length of 315±42 nm and a diameter of 6.2±1.6 nm;
[0073] 15 g of acrylamide monomer, 0.3 g of N,N'-methylenebisacrylamide (crosslinking agent), and 0.3 g of ammonium persulfate (catalyst) were dissolved in 100 mL of deionized water and mixed evenly; then 300 μL of N,N,N',N'-tetramethylethylenediamine (initiator) was added and mixed evenly, poured into a mold, polymerized at room temperature for 5 min, and then immersed in a large amount of deionized water to remove unreacted monomers and fully swell the mold to obtain a polyacrylamide hydrogel plate;
[0074] Place the obtained polyacrylamide hydrogel plate in a container, add 200 mL of 1 mol / L CaCl2 solution, soak for 1 hour, then take it out and place it on a clean glass plate;
[0075] Mixing cellulose nanocrystals CNC, sodium carboxymethyl cellulose CMC, sodium alginate SA and water to obtain a reaction solution, wherein the mass ratio of cellulose nanocrystals to sodium carboxymethyl cellulose is 10:100, the mass ratio of sodium carboxymethyl cellulose to sodium alginate is 10:6, the mass ratio of cellulose nanocrystals to water is 10:10000, the viscosity of sodium carboxymethyl cellulose is 3000-5000 mpa·s, and the viscosity of sodium alginate is 180-220 mpa·s;
[0076] The polyacrylamide hydrogel plate swollen to saturation is placed in an L shape, the syringes in the reaction liquid syringe array are connected to the vertical grooves on the hydrogel plate through pipelines one by one, the reaction liquid is placed in the reaction liquid syringe array, the reaction liquid is squeezed into the hydrogel groove from the syringe array, the gel fiber formed by flowing through the groove is passed through a water bath, and then dried in the air to obtain a cellulose nanocrystal composite material.
[0077] Example 2
[0078] A cellulose nanocrystal composite material was prepared in the manner of Example 1, wherein the mass ratio of cellulose nanocrystals to sodium carboxymethyl cellulose was 3:100.
[0079] Example 3
[0080] A cellulose nanocrystal composite material was prepared in the manner of Example 1, wherein the mass ratio of cellulose nanocrystals to sodium carboxymethyl cellulose was 5:100.
[0081] Example 4
[0082] A cellulose nanocrystal composite material was prepared in the manner of Example 1, wherein the mass ratio of cellulose nanocrystals to sodium carboxymethyl cellulose was 15:100.
[0083] The contents of the components in the cellulose nanocrystal composite materials obtained in Examples 1 to 4 are shown in Table 1;
[0084] Table 1 Content of each component in the cellulose nanocrystal composite material obtained in Example
[0085] CNC content / % SA content / % CMC content / % Example 1 5.8 35.3 58.9 Example 2 1.8 36.8 61.4 Example 3 3.0 36.4 60.6 Example 4 8.5 34.3 57.2
[0086] Comparative Example 1
[0087] A cellulose nanocrystal composite material was prepared in the manner of Example 1, wherein the angles between the hydrogel sheets were 180° (ie, the whole was placed in a horizontal direction) and 45°, respectively.
[0088] Comparative Example 2
[0089] A cellulose nanocrystal composite material was prepared in the manner of Example 1, wherein no cellulose nanocrystals were added, and the mass ratios of sodium alginate and sodium carboxymethyl cellulose were 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 and 0.9, respectively.
[0090] Performance Testing
[0091] Test Example 1
[0092] The composite fibers prepared with different hydrogel substrate groove inclination angles in Example 1 and Comparative Example 1 were tested, where 0° means the angle is 180°, and 90° means Example 1;
[0093] (1) Figure 2 Schematic diagram of preparation of different hydrogel substrate groove inclination angles in Example 1 and Comparative Example 1;
[0094] (2) Figure 3 The azimuth angle curves of the composite fiber samples prepared with different hydrogel substrate groove inclination angles in Example 1 and Comparative Example 1 are shown in FIG. Figure 3 It can be seen that the CNC in the composite fiber prepared at a tilt angle of 90° has an obvious (200) crystal plane orientation, so the orientation degree of CNC in the composite fiber prepared at this tilt angle is the best;
[0095] (3) Figure 4 The electron diffraction images of the composite fiber samples prepared with different hydrogel substrate groove inclination angles under different inclination angles in Example 1 and Comparative Example 1 are shown in FIG. Figure 4 It can be seen that the composite fiber prepared at a tilt angle of 90° has obvious birefringence, so the orientation degree of the composite fiber prepared at this tilt angle is the best;
[0096] (4) Figure 5 Polarized light microscope test pictures of composite fiber samples prepared with different hydrogel substrate groove inclination angles in Example 1 and Comparative Example 1. Figure 5 It can be seen that the orientation degree of cellulose nanocrystals in the composite fibers prepared at a tilt angle of 90° is the best;
[0097] (5) Figure 6 The orientation parameters calculated for the composite fiber samples prepared at different hydrogel substrate groove inclination angles in Example 1 and Comparative Example 1, at 0°, the orientation parameter of the SA-CMC-CNC fiber is 0.31±0.05; at an angle of 45°, the orientation parameter of the SA-CMC-CNC fiber is 0.58±0.06; at an angle of 90°, the SA-CMC-CNC fiber has the best orientation, with an orientation parameter of 0.87±0.07.
[0098] Test Example 2
[0099] Figure 7 The tensile stress-strain curves of the composite fibers prepared at different CMC-SA ratios in Comparative Example 2 are as follows: the test standard is ASTM D638, the specimen gauge length is 7.6 mm, the tensile rate is 5 mm / min, and the test is conducted at 25°C and a relative humidity of 45;
[0100] It can be seen that when the relative ratio of CMC-SA is 0.6, the mechanical properties of the composite fiber are the best, with a fiber strength of 581.1±13.1MPa, a strain of 5.4±0.2GPa, a Young's modulus of 11.2±1.2GPa, and a toughness of 17.3±0.3MJ·m -3 .
[0101] Test Example 3
[0102] Figure 8 The tensile stress-strain curves of the cellulose nanocrystal composite fibers obtained in Examples 1 to 4 are as follows: the test standard is the ASTM D638 test standard, the sample gauge length is 7.6 mm, the tensile rate is 5 mm / min, and the test is performed at 25°C and a relative humidity of 45; wherein 3% is Example 2, 5% is Example 3, 10% is Example 1, and 15% is Example 4, and the blank control (i.e., 0%) is taken as no cellulose nanocrystals added;
[0103] The specific results obtained are shown in Table 2;
[0104] Table 2 Mechanical properties of cellulose nanocrystal composite fibers obtained in Example
[0105]
[0106] It can be seen from Table 2 that the composite fiber with a CNC to CMC ratio of 10:100 has the best tensile strength.
[0107] Fig. 9 is the azimuth curve of the cellulose nanocrystal composite fiber obtained in Examples 1 to 4, Fig. 9 The obtained cellulose nanocrystal orientation parameters are shown in Table 3. It can be seen that the orientation degree of cellulose nanocrystals in the composite fiber with a CNC to CMC ratio of 10:100 is the best.
[0108] Fig.10 is the calculated orientation parameter of the cellulose nanocrystal composite fiber obtained in Examples 1 to 4, and the specific results are shown in Table 3;
[0109] Table 3 Orientation parameters of cellulose nanocrystal composite materials obtained in Example
[0110]
[0111]
[0112] Fig.11 The scanning electron microscope (SEM) image and element distribution diagram of the composite fiber obtained in Example 1 are shown in FIG. Fig.11 It can be seen that the cellulose nanocrystals are evenly distributed in the prepared composite fibers.
[0113] Fig.12 The decomposition of the composite fiber obtained in Example 1 on the paper tube and the decomposition rate of the paper tube are compared. The experimental results also show that the prepared nanocomposite fiber can be completely decomposed in ten days under natural conditions, while the wound paper tube is almost not decomposed. This shows that the prepared composite nanofiber has strong biodegradability.
[0114] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing cellulose nanocrystal composite fibers, characterized in that: The following steps are involved: A hydrogel plate is provided as a substrate, wherein a plurality of grooves arranged side by side are arranged on the surface of the substrate; the hydrogel plate is in an L-shaped structure; After the substrate is swelled to saturation in an aqueous solution containing calcium ions, a reaction solution is injected into the vertical grooves of the hydrogel plate, and the gel fibers formed by the grooves are bathed in water to obtain the cellulose nanocrystal composite fibers; The reaction solution comprises cellulose nanocrystals, water-soluble polymers, sodium alginate and water.
2. The preparation method according to claim 1, characterized in that: The hydrogel plate is a polyacrylamide hydrogel plate; the groove is a circular groove with a diameter of 0.4 to 1.0 mm.
3. The preparation method according to claim 1, characterized in that: The concentration of calcium ions in the calcium ion-containing aqueous solution is 0.5 to 3 mol / L.
4. The preparation method according to claim 1, characterized in that: The cellulose nanocrystal is in a nanorod structure, and the length of the nanorod structure is 315±42 nm and the diameter is 6.2±1.6 nm.
5. The preparation method according to claim 1, characterized in that: The water-soluble polymer includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose and water-soluble polyurethane.
6. The preparation method according to claim 5, characterized in that: The viscosity of the sodium carboxymethyl cellulose is 3000-5000 mpa·s; The weight average molecular weight of the polyvinyl alcohol is 14.6-18.6w; The solid content of the water-soluble polyurethane is 37-39%.
7. The preparation method according to claim 1, characterized in that: The viscosity of the sodium alginate is 180-220 mpa·s.
8. The preparation method according to claim 1, characterized in that: The mass ratio of the water-soluble polymer to sodium alginate is 10:3-10; When the water-soluble polymer is sodium carboxymethyl cellulose, the mass ratio of the cellulose nanocrystals to the water-soluble polymer is 3 to 15:100; When the water-soluble polymer is polyvinyl alcohol or water-soluble polyurethane, the mass ratio of the cellulose nanocrystals to the water-soluble polymer is 5 to 15:100; The mass ratio of the cellulose nanocrystals to water is 3-15:10000.
9. The preparation method according to claim 1, characterized in that: After the water bath, the obtained wet fibers are dried.
10. The device used in the preparation method according to any one of claims 1 to 9, characterized in that: include: A hydrogel plate, wherein a plurality of grooves arranged side by side are arranged on the surface of the hydrogel plate, and the hydrogel plate is in an L-shaped structure; A reaction liquid syringe array, wherein the syringes in the reaction liquid syringe array are connected to the vertical grooves on the hydrogel plate in a one-to-one correspondence through pipelines; Water bath.
Citation Information
Patent Citations
Preparation method of composite fiber of cellulose nanometer fibrils / alginate
CN106521706A
High-toughness nano composite fiber and preparation method thereof
CN117926445A
PRISTINE AND SURFACE FUNCTIONALIZED CELLULOSE NANOCRYSTALS (CNCs) INCORPORATED HYDROGEL BEADS AND USES THEREOF
US20160175812A1